The Role of Competence, Work Discipline and Work Environment Improving Employee Performance in Cooperatives in Jember Regency - Qomariah, Nurul; Nuriesty Putri Utamy (Universitas Dr. Soetomo, 2023)
Cooperatives are one of the privately owned enterprises that also participate in driving the nationaleconomy. This research was conducted at cooperatives throughout Jember Regency and had the aim ofbeing the first to test and find out the effect of the work environment (X) on work discipline. The secondgoal is to test and find out the effect of work discipline (Z) on employee performance, and the last goal isto test and find out the effect of the work environment (X) on employee performance (Y). The population ofthis research is all employees of cooperatives operating in Jember Regency, totaling 1488 employees. Thesample size was determined using the Slovin formula and the sample size was 315 respondents. Thesampling technique is to use probability sampling with the technique taken, namely proportional sampling for each active cooperative. Data analysis used included: descriptive analysis, analysis of validity and reliability tests, and analysis of hypotheses, all of which were processed using Partial Least Square (SEMPLS) with the Warp PLS 6.0 program. After being analyzed using Warp PLS, the findings of this study are that competence has an impact on employee performance. Meanwhile, work discipline has an impact on employee performance at cooperatives in Jember Regency. The work environment has an impact onemployee performance. Thus, the first hypothesis is accepted. The second hypothesis is accepted while the third hypothesis is accepted.